2014
DOI: 10.1016/j.jceh.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Treatment in the ‘Real-World’: How Well Do ‘Real’ Patients Respond?

Abstract: Background: Published clinical trials of the treatment of HCV are largely multicentre prospective pharmaceutical trials. Patients in clinical trials tend to have more favorable outcomes than patients in the 'real-world', due to strict patient selection and differences in treatment conditions and available resources. Objectives: To assess the outcomes of Hepatitis C infected patients treated at the Barwon Health Liver Clinic with combination Pegylated interferon (PEG-IFN) and Ribavirin (RBV) therapy and to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…With regard to hepatitis C virus, gaps between the efficacy and effectiveness of hepatitis C virus treatment are substantial; treatment efficacy rates generally exceed 90%, while numerous reports find net effectiveness often under 20%. [40, 41]…”
Section: 0 Significance Of Distinguishing Effectiveness and Efficacmentioning
confidence: 99%
“…With regard to hepatitis C virus, gaps between the efficacy and effectiveness of hepatitis C virus treatment are substantial; treatment efficacy rates generally exceed 90%, while numerous reports find net effectiveness often under 20%. [40, 41]…”
Section: 0 Significance Of Distinguishing Effectiveness and Efficacmentioning
confidence: 99%
“… 50 s Presented as intravenous drug use mode of acquisition. 25 Abbreviations: ALT, alanine aminotransferase; BMI, body mass index; CAD, coronary artery disease; GI, gastrointestinal; HAART, highly active antiretroviral therapy; HCV, hepatitis C virus; HIV, human immunodeficiency virus; PCP, primary care provider; PTSD, posttraumatic stress disorder; RNA, ribonucleic acid; STD, sexually transmitted disease; SVR, sustained viral response. …”
Section: Figurementioning
confidence: 99%
“…These new regimens have been tested in controlled trials, where patients tend to have relatively more favorable outcomes. 25 The effectiveness of these regimens in clinical practice must be determined. Outcomes research studies have shown that patient outcomes are affected by multiple factors, including the health care processes that are recommended in guidelines for the management of HCV infection.…”
Section: Introductionmentioning
confidence: 99%